Mapping the landscape of halal tourism: a bibliometric analysis - Chariyada Chantarungsri; Nongluck Popichit; Sanasun Rugthangam; Nuanrath Wattana; Jirat Chuanchom; Monsinee Sukmak (Cogent Social Sciences)
This study conducts a bibliometric analysis of Halal tourism research from 2013 to 2023. Using Scopus data and tools like Microsoft Excel, Endnote, and VOSViewer, 304 articles were analyzed to map key themes, influential publications, and research collaborations, providing a comprehensive overview of the field’s evolution and landscape. Key findings reveal exponential growth in publications, highlighting influential works such as those by Battour M. in Tourism Management Perspectives. Analysis of 67 highly-cited authors identifies four main schools of thought: Islamic principles, customer satisfaction, risk management, and Muslim tourist experiences. Keyword analysis identifies dominant themes such as Halal certification and food, suggesting emerging opportunities in heritage tourism and technology integration. The study identifies key research gaps, advocating for investigations into heritage tourism’s intersection with Halal tourism, the impact of Halal certification, and technology’s role in enhancing travel experiences. Policy recommendations include fostering welcoming environments for Muslim travelers, streamlining Halal certification, and promoting cultural attractions. The findings offer practical implications for stakeholders and policymakers, providing a basis for further exploration and development in the Halal tourism industry.